2022
DOI: 10.1093/cdn/nzac135
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Determinants of Dietary Diversity in Children Aged 6–59 Months in Ethiopia: Analysis of 2005–2016 Demographic and Health Survey

Abstract: Background Dietary diversity can indicate child's health and optimum growth. Objective To analyze the trends and determinants of minimum dietary diversity (MDD) among children aged 6 to 59 months in Ethiopia. Methods Ethiopian Demographic Health Survey (EDHS) data of three consecutive years (2005, 2011 and 2016) were analyzed. A total of N = 2,396 (2005), N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Previous studies which were conducted to assess dietary diversity among children in Ethiopia investigated the consumption of fruits and vegetables rich in Vitamin A as a single food group, and other fruits and vegetables as another food group and, among other food groups as part of the overall diet. Most of these studies demonstrate low consumption of fruits and vegetables among children age 6-23 months [17][18][19][20][21][22]. For example a study conducted in southern Ethiopia reported 7.2% and 39.1% respectively of children who consumed Vitamin A rich, and other fruits and vegetables the day prior to the survey [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies which were conducted to assess dietary diversity among children in Ethiopia investigated the consumption of fruits and vegetables rich in Vitamin A as a single food group, and other fruits and vegetables as another food group and, among other food groups as part of the overall diet. Most of these studies demonstrate low consumption of fruits and vegetables among children age 6-23 months [17][18][19][20][21][22]. For example a study conducted in southern Ethiopia reported 7.2% and 39.1% respectively of children who consumed Vitamin A rich, and other fruits and vegetables the day prior to the survey [18].…”
Section: Introductionmentioning
confidence: 99%
“…“Minimum dietary diversity is defined as consumption of food from four or more out of seven food groups for higher dietary quality and to meet daily energy and nutrient requirements of the seven recommended food groups namely : grains , roots and tubers; legumes and nuts; dairy products; flesh foods (meat , fish , poultry and organ meat) , eggs; vitamin-A rich fruits and vegetables; other fruits and vegetables” Minimum dietary diversity is one of the eight indicators of infant and young child feeding practices as proposed by the World Health Organization [ 11 ]. Increased variety of dietary intake is usually proportional to improved diet quality, characterized by more animal-source foods than a less diversified one [ 12 ]. Consistent intake of diverse food sources is essential for adequately meeting nutrient demands [ 13 ].…”
Section: Introductionmentioning
confidence: 99%